The tide-dominated Han River Delta, Korea : geomorphology, sedimentology, and stratigraphic architecture - Cummings, Don I.; Dalrymple, Robert W. (Robert Walker); Kyungsik, Choi; Jin, Jae Hwa (Elsevier, 2016)
The Tide-Dominated Han River Delta provides a thorough analysis of a river delta in which tidal currents have reworked the river-borne sediment, generating characteristic geomorphological and sedimentological signatures in the process. Such "tide-dominated" deltas are common in the modern ocean, forming the substrate upon which entire populations are built. Furthermore, ancient examples contain enormous volumes of hydrocarbon. Despite this, tide-dominated deltas remain less well understood than their wave- and river-dominated counterparts, largely because processes within them are inherently more complex and fewer modern examples have been investigated in detail. This multi-year study by a team of experts in coastal geoscience represents the most complete documentation of a tide-dominated delta to date. Results help advance, and are applicable to, a broad range of fields within sedimentary geology, including clastic sedimentology, seismic and sequence stratigraphy, and coastal geomorphology, in addition to petroleum geology and reservoir engineering. Offers new access to results of a multi-year hydrocarbon-reservoir analogue study not available elsewhere Features 75 full-color figures and illustrations to emphasize critical aspects of the delta's sedimentology, geomorphology, and stratigraphy Provides basic data that better define what tide-dominated deltas are, how these complex systems behave over time, and why this is so Aids petroleum geologists and reservoir engineers in predicting the distribution of baffles and barriers in tide-dominated sediment bodies, helping in the successful development of reservoirs.